2021
DOI: 10.7150/ntno.52168
|View full text |Cite
|
Sign up to set email alerts
|

MR-labelled liposomes and focused ultrasound for spatiotemporally controlled drug release in triple negative breast cancers in mice

Abstract: Rationale: Image-guided, triggerable, drug delivery systems allow for precisely placed and highly localised anti-cancer treatment. They contain labels for spatial mapping and tissue uptake tracking, providing key location and timing information for the application of an external stimulus to trigger drug release. High Intensity Focused Ultrasound (HIFU or FUS) is a non-invasive approach for treating small tissue volumes and is particularly effective at inducing drug release from thermosensitive nanocarriers. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…PET, MR and fluorescence imaging have great potential to be used in these studies. Fluorescence imaging can be used for short-term realtime biodistribution imaging in small animals 123 whereas PET imaging has clinical translatability for large animals and human. Besides, PET allows treatment monitoring and planning.…”
Section: Phase Change Nanodroplets For Bioimagingmentioning
confidence: 99%
“…PET, MR and fluorescence imaging have great potential to be used in these studies. Fluorescence imaging can be used for short-term realtime biodistribution imaging in small animals 123 whereas PET imaging has clinical translatability for large animals and human. Besides, PET allows treatment monitoring and planning.…”
Section: Phase Change Nanodroplets For Bioimagingmentioning
confidence: 99%
“…In another study, gadolinium- and DOX-loaded liposomes were activated upon HIFU exposure, in which they release about whole encapsulated MRI contrast and anticancer contents. The MDA-MB-231 tumor-bearing mice treated with the liposomes and HIFU experienced a significant inhibition in tumor growth ( Amrahli et al, 2021 ).…”
Section: Liposomes For Delivery Of Therapeutic and Imaging Agentsmentioning
confidence: 99%
“…A more recent study reported a Gd-labeled thermoresponsive liposome that can be concentrated in a tumor. 71 A subsequent burst of focused US (3 minutes) caused it to release a DOX payload, thus allowing highly targeted treatment. The accumulation of liposomes at the tumor site also caused a reduction of the T 1 relaxation time.…”
Section: Mri-guided Us Thermal Therapymentioning
confidence: 99%
“…This was found able to act as a radiofrequency thermal therapy agent, which can trigger the release of DTX as observed in T 2 ‐weighted MRI and eradicate the cancer cells by heat energy generated from radiofrequency irradiation. A more recent study reported a Gd‐labeled thermoresponsive liposome that can be concentrated in a tumor 71 . A subsequent burst of focused US (3 minutes) caused it to release a DOX payload, thus allowing highly targeted treatment.…”
Section: Theranostics For Mri‐guided Thermal Therapymentioning
confidence: 99%